Report on industrial attachment with Levi Strauss Asia Pacific Division Information Technology - Lim, Alvin Kar Keng. (2009)
This report provides details and encounters during my 22-week attachment. Levi Strauss Asia Pacific Division IT Department provides support and applications to all the affiliate countries in the Asia Pacific Region, namely Indonesia, HongKong, Malaysia, Philippines, Australia, New Zealand, Pakistan, India, South Africa, Taiwan, Korea and Japan. During these 22 weeks, I was given a chance to support Hong Kong in a upgrading project for all the Asia Pacific affiliates. This attachment also exposed me to many technical issues of desktops and laptops faced by users. I was able to experience how IT enhances an apparel company and making it one of the leading clothing brand in the world.